College Women, Sex, and Drinking: Examining the Impact of Pre-sex Alcohol Consumption in Consensual Sexual Encounters. (1st August 2022) - Conroy, K; Blayney, J; George, W; Bird, E
ABSTRACT: Introduction: College is a time of sexual exploration and experimentation for many emerging adults. Sex and alcohol use frequently co-occur on college campuses. Research and theory predict that alcohol catalyzes sexual responding and enjoyment, despite evidence linking alcohol with negative sexual outcomes. Because of this apparent paradox, research examining different facets of post-drinking sexuality continues to warrant attention. Objective: The purpose of this study is to examine whether alcohol-involved sexual encounters differ from non-alcohol-involved ones in terms of sexual distress, sexual functioning, and sex-related consequences. Methods: First- and second-year college women (N = 389) were enrolled in a longitudinal study on college women's alcohol use and sexual health. Inclusion criteria included having sex with a man and drinking alcohol in the 3 months prior to study enrollment. Study participation entailed the completion of a baseline survey and follow-up surveys at 6 and 12 weeks. At each timepoint, participants answered event-specific questions regarding their most recent sexual encounter. Participants who reported at least one sexual encounter over the course of the study (n = 351) were included in analyses. Participants completed measures of sexual distress and sexual consequences. Sexual functioning and satisfaction were measured using the Monash Female Sexual Satisfaction Questionnaire. Estimated blood alcohol concentration (e-BAC) at the time of the sexual encounter was also calculated. Results: Across the study, participants reported 758 unique sexual encounters, ranging from 1-3 events per participant (M = 2.16, SD = .84). Alcohol was consumed in 429 (57%) of the sexual encounters reported. Most encounters took place with a partner with whom the participant had sex previously (83%) and with a boyfriend (62%). Encounters that were preceded by alcohol consumption were more likely to be with a new partner, X2(1, N=745) = 17.68, p < .001, or non-boyfriend, X2(1, N=737) = 57.98, p < .001. Most encounters (86%) included receptive vaginal or anal penetration. Among those who drank prior to the sexual encounter, e-BAC ranged from .00 to .27% (M = .06, SD = .06). Alcohol-involved sexual encounters led to fewer positive sexual consequences, t(692) = 2.54, p = .003 and with higher sexual distress, t(720) = .689, p = .012. There was a trend toward more negative sexual consequences (e.g. concern about STIs, unwanted pregnancy, worsened mood) following alcohol-involved encounters, t(660) = -1.37, p = .044, though this difference is not significant following Bonferroni correction (α = .013). There were no significant differences in overall sexual functioning. Conclusions: Sex under the influence of alcohol is common among college women and is associated with more distress and fewer positive consequences than sober sexual encounters. Women who drink prior to sex may do so for a variety of reasons, including to enhance sexual pleasure or to cope with distress or anxiety around sex. Sexual health professionals are encouraged to query patients about their alcohol use, particularly in sexual contexts, and to provide psychoeducation and alternative strategies to enhance sexual experiences without alcohol. Disclosure: No